Comparative Study of Yi Lacquerware Characteristics in Two Regions and Its Application in Modern Art Design - Zhao, Qiqi (UNIMAS, 2025)
This study explores the artistic characteristics of Yi lacquerware, a significant expression of Yi cultural heritage. It focuses on molding techniques, decorative patterns, and color schemes that reflect the creativity and cultural identity of the Yi people. The research compares lacquerware from two important regions: Liangshan Prefecture in Sichuan Province and Dafang County in Guizhou Province. It identifies both the distinct differences and shared features in their artistic styles. These variations are influenced by geographical conditions, ethnic identity, cultural traditions, religious beliefs, and the growth of local lacquer industries. The study emphasizes how these elements contribute to the development and transformation of regional artistic styles. It also discusses current challenges, such as maintaining a balance between preserving tradition and encouraging innovation. In addition, it investigates strategies for incorporating Yi lacquerware into contemporary art and design. Using a combination of literature review, field research, interviews, comparative analysis, and case studies, the study offers a comprehensive understanding of the artistic and cultural significance of Yi lacquerware. The findings support the long-term development of traditional crafts and provide valuable insights for applying Yi lacquerware in modern design contexts.